Effective phonon scattering and enhancement of thermoelectric performance in Ga-excess Bi0.4Sb1.6Te3 compounds - Back, Song Yi; Cho, Hyunyong; Byeon, Seokyeong; Jin, Hyungyu; Rhyee, Jong-Soo (Current applied physics, 2020)
We investigate the thermoelectric properties on Ga-excess p-type GaxBi0.4Sb1.6Te3 compounds. Even though the random distribution of Ga-doping increases electrical resistivity giving rise to the decrease of power factor, the significant decrease of lattice thermal conductivity by the excess Ga-doping induces significant enhancement of ZT value (1.13 at 350 K) for the Ga x = 0.03 doped compound. From the X-ray diffraction and elemental mapping by energy dispersive X-ray spectroscopy, we observed Sb and Ga phase separation leading to the phonon scattering. The Sb precipitation implies atomic defect in the matrix which can induce short wavelength phonon scattering. The synergetic phonon scatterings from various scattering sources such as point defect, alloy scattering, and grain boundary phonon scattering have an important role in the enhancement of thermoelectric performance. [Display omitted] •We investigate the thermoelectric properties on Ga-excess p-type Ga-excess Bi0.4Sb1.6Te3 compounds.•Significant decrease of lattice thermal conductivity and high ZT value (1.13 at 350 K) for the Ga x = 0.03 doped compound.•We observed Sb and Ga phase separation leading to the phonon scattering.•The synergetic phonon scatterings from various scattering sources enhances thermoelectric performance.